Cultura e comportamentos de cidadania organizacional em uma instituição de ensino superior: uma aplicação de modelagem de equações estruturais - VASCONCELLOS, Caitto Arroyo (Universidade Federal do Pará, 2025)
This study aims to analyze how different cultural characteristics impact Organizational Citizenship Behavior (OCB) in Higher Education Institutions (HEIs). To achieve this, an exploratory-descriptive survey of a quantitative nature was conducted among 401 employees of a Federal University located in the state of Pará, Brazil. The questionnaire utilized the Organizational Culture Assessment Instrument (OCAI) and Organizational Citizenship Behavior (OCB) scales. Data were processed using the partial least squares structural equation modeling (PLS-SEM) technique through SmartPls4® software. Results indicated a prevalence of hierarchical and clan cultures, along with high OCB scores, both individual-focused (OCBI) and organization-focused (OCB-O). It was concluded that OCB-I is positively and significantly influenced by clan (H1a), adhocratic (H3a), and market (H4a) cultures, while OCB-O is influenced by clan (H1b), hierarchical (H2a), and adhocratic (H3b) cultures. The research contributes theoretically to understanding the role of OCB and its interrelation in the workplace. The expectation is that these findings guide managers in formulating organizational strategies, especially in the public sector.